2010
DOI: 10.1093/deafed/enq017
|View full text |Cite
|
Sign up to set email alerts
|

Using Miscue Analysis to Assess Comprehension in Deaf College Readers

Abstract: For over 30 years, teachers have used miscue analysis as a tool to assess and evaluate the reading abilities of hearing students in elementary and middle schools and to design effective literacy programs. More recently, teachers of deaf and hard-of-hearing students have also reported its usefulness for diagnosing word- and phrase-level reading difficulties and for planning instruction. To our knowledge, miscue analysis has not been used with older, college-age deaf students who might also be having difficulty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
0
15
0
10
Order By: Relevance
“…Literacy development in children with severe-profound hearing loss has historically been poor, with reports of many children unable to read beyond fourth-grade elementary level (Geers et al, 2008;Moeller et al, 2007), and 30% of children functionally illiterate when they graduate from secondary school (Traxler, 2000). Even very recent studies of university students with hearing loss, who are presumably among students with the best academic outcomes, have revealed that reading abilities in this population are still below the sixth grade level (Albertini & Mayer, 2011;Parault & Williams, 2010). It has been documented that reading development in many children with hearing loss plateaus at Chall's stage three (Marschark & Harris, 1996), resulting in ongoing difficulties with 'reading to learn', and a lack of ability to use both top-down and bottom-up processing, all of which reduce comprehension and the ability to acquire new knowledge.…”
Section: Readingmentioning
confidence: 99%
“…Literacy development in children with severe-profound hearing loss has historically been poor, with reports of many children unable to read beyond fourth-grade elementary level (Geers et al, 2008;Moeller et al, 2007), and 30% of children functionally illiterate when they graduate from secondary school (Traxler, 2000). Even very recent studies of university students with hearing loss, who are presumably among students with the best academic outcomes, have revealed that reading abilities in this population are still below the sixth grade level (Albertini & Mayer, 2011;Parault & Williams, 2010). It has been documented that reading development in many children with hearing loss plateaus at Chall's stage three (Marschark & Harris, 1996), resulting in ongoing difficulties with 'reading to learn', and a lack of ability to use both top-down and bottom-up processing, all of which reduce comprehension and the ability to acquire new knowledge.…”
Section: Readingmentioning
confidence: 99%
“…These students cannot be assessed using an English‐based assessment that does not take into consideration the differences between ASL and English. To further compound on the differences in languages, students who use both spoken English and ASL signs tend to show struggles in modifying sentence structures (Albertini & Mayer, ).…”
Section: Running Recordsmentioning
confidence: 99%
“…This approach, while not widely used, has been shown to provide a more authentic representation of Deaf children's reading abilities (Luft, ). The use of miscue analysis also provides information to identify specific areas of reading which are impacting the students’ ability to comprehend text (Albertini & Mayer, ).…”
Section: Miscue Analysismentioning
confidence: 99%
See 2 more Smart Citations